Pemberdayaan Kelompok Wanita Tani dalam Upaya Menumbuhkan Minat Wirausaha - Teti Susilowati; Muryanto Agus Nuswantoro; Emy Susiatin (CV. Multi Kreasi Media, 2022)
The objectives of this service activity are: 1) Provide motivation and increase entrepreneurial knowledge and make alternative sources of additional income for families through socialization. 2) Providing knowledge skills to women in the Women's Farmer Group in Kedungpane Village, Mijen District, Semarang City about innovations in making various preparations with cassava as basic ingredients by conducting product manufacturing demonstrations. The PKM program was carried out in RW 01, Kedungpane Village, Mijen District, Semarang City. The method used was socialization through activities in several stages, including: preparation stage, implementation stage and evaluation. The results of the evaluation are based on the results of the questionnaires that have been filled out by the participants that most of the responses are from their opinions. The results of the questionnaires that have been filled out by the participants are that most of the responses from their opinions include: being interested in doing business and innovating processed cassava, getting benefits and new knowledge and want more socialization about how to market the product